The three-minute classroom walk-through : changing school supervisory practice one teacher at a time - Downey, Carolyn J. (Thousand Oaks, CA : Corwin Press, 2004)
Describes a model for classroom walk-throughs designed to change how principals approach supervision, moving from the supervisor-subordinate relationship, to one based on an exchange between adults in professional practice.
Includes bibliographical references (p. 187-193) and index.
Professional
Keywords: Observation (Educational method); Reflection (Philosophy); School supervision; Teacher-principal relationships; Reflection (Philosophy); School supervision; Schools -- Administration; Teachers -- Training